Targeting NUPR1-dependent stress granules formation to induce synthetic lethality in KrasG12D-driven tumors - Santofimia-Castaño, Patricia; Fraunhoffer, Nicolas; Liu, Xi; Bessone, Ivan Fernandez; di Magliano, Marina Pasca; Audebert, Stephane; Camoin, Luc; Estaras, Matias; Brenière, Manon; Modesti, Mauro; Lomberk, Gwen; Urrutia, Raul; et al. (EMBO molecular medicine, 2024)
We find that NUPR1, a stress-associated intrinsically disordered protein, induced droplet formation via liquid–liquid phase separation (LLPS). NUPR1-driven LLPS was crucial for the creation of NUPR1-dependent stress granules (SGs) in pancreatic cancer cells since genetic or pharmacological inhibition by ZZW-115 of NUPR1 activity impeded SGs formation. The Kras G12D mutation induced oncogenic stress, NUPR1 overexpression, and promoted SGs development. Notably, enforced NUPR1 expression induced SGs formation independently of mutated Kras G12D . Mechanistically, Kras G12D expression strengthened sensitivity to NUPR1 inactivation, inducing cell death, activating caspase 3 and releasing LDH. Remarkably, ZZW-115-mediated SG-formation inhibition hampered the development of pancreatic intraepithelial neoplasia (PanINs) in Pdx1-cre;LSL-Kras G12D (KC) mice. ZZW-115-treatment of KC mice triggered caspase 3 activation, DNA fragmentation, and formation of the apoptotic bodies, leading to cell death, specifically in Kras G12D -expressing cells. We further demonstrated that, in developed PanINs, short-term ZZW-115 treatment prevented NUPR1-associated SGs presence. Lastly, a four-week ZZW-115 treatment significantly reduced the number and size of PanINs in KC mice. This study proposes that targeting NUPR1-dependent SGs formation could be a therapeutic approach to induce cell death in Kras G12D -dependent tumors. Synopsis Activation of kras oncogene induces, on one hand, a strong oncogenic stress, and on the other hand, a concomitant stress response, including the activation of the stress protein NUPR1, which in turn induces the formation of SGs through its ability to undergo LLPS. Enforced NUPR1 expression induced SGs formation, independently of mutated KrasG12D, which played a protective role in the cell. Inhibition of ZZW-115-mediated SGs-formation hampered the development of PanINs in Pdx1-cre;LSL-KrasG12D (KC) mice. ZZW-115-treatment of KC mice triggered caspase 3 activation, DNA fragmentation, and formation of apoptotic bodies, leading to cell death, specifically in KrasG12D-expressing cells. Targeting NUPR1-dependent SGs formation could be a therapeutic approach to induce cell death in KrasG12D-dependent tumors. Activation of kras oncogene induces, on one hand, a strong oncogenic stress, and on the other hand, a concomitant stress response, including the activation of the stress protein NUPR1, which in turn induces the formation of SGs through its ability to undergo LLPS.